COMPARATIVE GROWTH PERFORMANCE AND ECONOMIC EFFICIENCY OF INDIGENOUS ASEEL VARIETIES FED ON DIFFERENT DIETARY LYSINE REGIMENS - T. Batool; N. Roohi; A. Mahmud (Journal of Animal and Plant Sciences, 2018)
This study was planned to investigate the growth performance and economic efficiency of Lakha, Mianwali, Mushki and Peshawari varieties of Indigenous Aseel Chicken. For this purpose, 240 day old Aseel chicks 60 from each variety were selected and kept under randomized complete block design having factorial arrangement of 20 replicates with one bird in each [4(varieties)×3( lysine regimens)×20(replicates)=240]. Each of the 20 birds from four varieties were fed on lysine regimens containing 1.3 % lysine (L1) for 6 weeks, 1.4% and 1.2 % (L2) each for 3 weeks and 1.5%, 1.3%, 1.1% lysine (L3) each for subsequent 2 weeks. Data regarding different growth parameters were collected and analyzed by ANOVA technique while Duncans Multiple Range (DMR) Test was applied to compare the treatment means. The economic efficiency was also calculated. Significant (P<0.05) differences were observed in body weight, weight gain, FCR and feed efficiency (FE) of birds fed with L3 lysine regimen while the overall growth performance was better in Mushki variety of Aseel. The current study revealed that Mushki Aseel should be preferred in terms of its better growth performance while Lysine is better to be fed in L3 regimen. due to increased growth (Abbas et al., 2016) . Usually
Keywords: Lysine regimens; Aseel varieties; Growth; Livability and Economic efficiency.